2002
DOI: 10.1038/sj.mp.4001130
|View full text |Cite
|
Sign up to set email alerts
|

Substance P receptor antagonist and clomipramine prevent stress-induced alterations in cerebral metabolites, cytogenesis in the dentate gyrus and hippocampal volume

Abstract: The neuropeptide substance P and its receptor, the neurokinin 1 receptor (NK 1 R) have been proposed as possible targets for new antidepressant therapies. The present study investigated the effect of the NK 1 R antagonist L-760,735 and the tricyclic antidepressant clomipramine in the chronic psychosocial stress paradigm of adult male tree shrews. Animals were subjected to a 7-day period of psychosocial stress before the onset of daily oral administration of L-760,735 (10 mg kg −1 day −1 ) or clomipramine (50 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
60
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(70 citation statements)
references
References 58 publications
10
60
0
Order By: Relevance
“…Our findings regarding the hippocampus are consistent with those of recent studies that report a profound effect of dentate gyrus neurogenesis in different models of depression and in different experimental animals, including intruder stress in marmosets (Gould et al, 1998), psychosocial stress in tree shrews (Czeh et al, 2001;van der Hart et al, 2002), and, in rodents, social defeat , footshock stress (Malberg and Duman, 2003), and chronic mild stress (Alonso et al, 2004). In addition, the decreased neurogenesis induced by inescapable stress correlates with behavioral despair several days after exposure to stress in the learned helplessness model of depression (Malberg and Duman, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings regarding the hippocampus are consistent with those of recent studies that report a profound effect of dentate gyrus neurogenesis in different models of depression and in different experimental animals, including intruder stress in marmosets (Gould et al, 1998), psychosocial stress in tree shrews (Czeh et al, 2001;van der Hart et al, 2002), and, in rodents, social defeat , footshock stress (Malberg and Duman, 2003), and chronic mild stress (Alonso et al, 2004). In addition, the decreased neurogenesis induced by inescapable stress correlates with behavioral despair several days after exposure to stress in the learned helplessness model of depression (Malberg and Duman, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…In the tree shrew the decrease in neurogenesis and overall hippocampal volumen by psychological stress was reversed by chronic treatment with tianeptine or clomipramine (Czeh et al, 2001;van der Hart et al, 2002). Chronic fluoxetine treatment reversed a decrease in neurogenesis in U-Es, unchallenged escitalopram; U-V, unchallenged vehicle; CMS-V, stress vehicle; CMS-Es-R, stress escitalopram responders; CMS-Es-NR, stress escitalopram nonresponders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that chronic treatment with antidepressants reverses stress-induced inhibition of neurogenesis in the hippocampal formation (van der Hart et al, 2002;Malberg and Duman, 2003;Alonso et al, 2004;Fuchs et al, 2004;Czeh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the effects of other well-established antidepressants, such as fluoxetine and clomipramine, have been successfully investigated on neurogenesis in animals submitted to various stress. 21,23,57 What kind of mechanism could subserve these effects? Recent data suggest that antidepressants facilitate activity-dependent selection of functional synaptic connections in brain and, through their neurotrophic effects, improve information processing within neuronal networks compromised in mood disorders.…”
Section: Neurobiological Properties Of Tianeptinementioning
confidence: 99%
“…10,20 Neurogenesis in the dentate gyrus of the hippocampal formation may be involved in the mechanism of action of a wide range of antidepressants. [21][22][23] This fascinating finding requires further research in order to understand how the mechanism of antidepressant treatments might converge to regulate common events such as neurogenesis and other forms of structural plasticity. Moreover, the concept of a serotonergic deficit in depression is particularly challenged by the drug tianeptine (S-1574, [3-chloro-6-methyl-5,5-dioxo-6,11-dihydro-(c,f)-dibenzo-(1,2-thiazepine)-11-yl) amino]-7 heptanoic acid, sodium salt), an antidepressant with structural similarities to the tricyclic antidepressant agents but with different pharmacological properties.…”
mentioning
confidence: 99%